2000
DOI: 10.1128/aac.44.9.2471-2474.2000
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimers, a New Class of Candidate Topical Microbicides with Activity against Herpes Simplex Virus Infection

Abstract: Dendrimers are large highly branched macromolecules synthesized from a polyfunctional core. They have shown a variety of biological properties, including, in some instances, antiviral activity. In this study, five dendrimers were evaluated for in vitro activity against herpes simplex virus (HSV) types 1 and 2 by cytopathic effect (CPE) inhibition and plaque reduction (PR) assay in human foreskin fibroblast cells. All of the compounds were active against both virus types in the CPE inhibition assay, in which dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(127 citation statements)
references
References 15 publications
2
124
0
1
Order By: Relevance
“…Among these, dendrimers and dendrimer-like molecules have recently been generated with surfaces formed of negative charges and screened for potential anti-herpes activities. Indeed, in vitro analysis has revealed that sulfonated and carboxylated polylysine dendrimers effectively block the HSV-1 and -2 infection of cells and non-primate animal studies have shown that they were able to protect animals against an intravaginal HSV-2 challenge (Bourne et al, 2000;Bernstein et al, 2003;Gong et al, 2005). However, in addition to inhibiting the HSV attachment, the sulfonate ddendrimers were also shown to act at a post-entry level by apparently inhibiting HSV DNA synthesis, which suggests that they could be used not only for prevention of HSV infection but also as inhibitors of viral replication (Gong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, dendrimers and dendrimer-like molecules have recently been generated with surfaces formed of negative charges and screened for potential anti-herpes activities. Indeed, in vitro analysis has revealed that sulfonated and carboxylated polylysine dendrimers effectively block the HSV-1 and -2 infection of cells and non-primate animal studies have shown that they were able to protect animals against an intravaginal HSV-2 challenge (Bourne et al, 2000;Bernstein et al, 2003;Gong et al, 2005). However, in addition to inhibiting the HSV attachment, the sulfonate ddendrimers were also shown to act at a post-entry level by apparently inhibiting HSV DNA synthesis, which suggests that they could be used not only for prevention of HSV infection but also as inhibitors of viral replication (Gong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[31] Similar results were obtained by Bourne and colleagues upon administration of sulfonated (BRI-2999) and carboxylated (BRI-6741) dendrimers (Figure 3d) to mice prior to exposure to HSV. [68] Recently, Dixon and colleagues [69] have reported inhibitory action of sulfonated naphthyl polyphyrins against HIV infection of cells in vitro. Besides polyanionic dendrimers, unmodified polycationic PAMAM dendrimers have also been shown to inhibit viral replication by disrupting the interaction between HIV Tat protein and transacting response element (TAR) RNA, which is crucial in the life cycle of HIV-1.…”
Section: Prevention Of Virus Binding To the Target Cell Surfacementioning
confidence: 99%
“…In most cases, Dendrimers have the ability of carrying biologically active agents by encapsulating them in the interior or generally, attaching them on the periphery of dendrimers. For example, most dendrimers displaying antimicrobial activities are terminated with antimicrobial agents, including ferrocene (Abd-Elzaher & Ali, 2006), quaternary ammonium , boron complexes (De Queiroz, 2006), carbohydrates (Rojo, 2004), and peptides (Bernstein et al, 2003, Bourne et al, 2000Janiszewska et al, 2006;Klajnert et al, 2006;Pini et al, 2005;Sechi et al, 2006).…”
Section: Dendrimers As Antibacterial or Antimicrobial Agentsmentioning
confidence: 99%